Sanksi Riddah Perspektif Maqasid Al-Shari’ah - Imroatul Azizah (Prodi Siyasah (Hukum Tata Negara) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2015)
Abstract: Riddah (apostasy), in the classical literatures of Islamic Jurisprudence, is categorized as a jarimah al-hudud (criminal act) with death penalty as the punishment. The fundamental issue is that the threat of the death penalty is only based on a single prophetic tradition, while it should be determined by the absolute and valid texts. It means that the death penalty is rooted to an absolute legal argumentation (qatâ€™i al-dalalah), while, there is none of the verses of al-Qurâ€™an which discusses about punishment for the perpetrator of apostasy. Otherwise, al-Qurâ€™an absolutely guaranteesthe freedom of religion and belief. This research uses maqasid al-shariâ€™ah (purposes of Islamic law)as an approach to see the purpose, spirit, and essential valueof the text to be a foundation and method in Islamic legal reasoning. The results of the research are: first, adopting what has been stipulated in al-Qurâ€™an textually and formally without appreciating its purpose and wisdom is not wise; second, apostasy, which is a kind of a private matter between a servant and his God, should not be categorized as a jarimah al-hudud but as a jarimah taâ€™zir (undefined crime). In certain condition, however, apostasy could be charged by a maximum penalty (death penalty) if it is accompanied by other crimes and is worthyto be sentenced based on a judgeâ€™s argumentation. Keywords: Apostasy, sanctions, maqasid al-shariâ€™ah Â Abstrak: Riddah dalam literatur fiqih klasik dikategorikan sebagai jarimah hudud, dan diancam dengan hukuman mati. Persoalan yang mendasar adalah ancaman hukuman mati tersebut hanya berdasarkan hadis ahad, padahal hudud dikonsepsikan sebagai jarimah dan hukuman yang telah ditentukan secara pasti oleh nass. Berarti hudud meniscayakan dalil yang qatâ€™i al-dalalah, sedangkan dalam al-Qurâ€™an tidak ada satu ayat pun yang membahas hukuman duniawi untuk pelaku riddah, sebaliknya al-Qurâ€™an justru memberikan jaminan kebebasan beragama dan berkeyakinan secara mutlak. Maqasid al-shariâ€™ah dipilih sebagai pendekatan untuk melihat bagaimana tujuan, ruh, dan nilai-nilai esensial shariâ€™at dijadikan landasan dan patokan utama dalam penentuan hukum Islam. Dengan pendekatan maqasid al-shariâ€™ah, diperoleh kesimpulan bahwa bukanlah sikap yang bijak ketika mengadopsi apa yang ditetapkan dalam nass secara literal dan formal legalistik tanpa mengapresiasi tujuan serta hikmah terdalam dari hukum tersebut. Riddah yang merupakan persoalan pribadi antara hamba dengan Tuhan-Nya, tidak selayaknya dikategorikan sebagai jarimah hudud. Namun sebagai jarimah taâ€™zir, riddah bisa dikenakan hukuman maksimal (mati) jika disertai dengan kejahatan lain yang menurut hakim harus dijatuhi hukuman tersebut.